Nuclear protein import in a permeabilized cell assay - Melchior, Frauke (Protein targeting protocols, 1998)
An in vitro nuclear import assay, using digitonin-permeabilized cells, grown on cover slips, and supplemented with exogenous cytosol and fluorescent-transport ligand, was developed in our laboratory several years ago (1). For a general introduction into this technique and references for alternative assays developed by other laboratories, see refs. 2 and 3. Although the original assay faithfully reproduces transport, quantitation by methods such as densitometry on photographic negatives or ACAS (anchored cell analysis and sorting) interactive laser cytometry is a rather time-consuming process. Another disadvantage of the original assay involving attached cells is that the number of cells per assay cannot easily be controlled. Both problems are circumvented by using a modification of the import assay recently developed by Paschal and Gerace (4), and described in detail below. Here, suspension cells are used as the source for permeable cells, and relative transport rates are determined rapidly by flow cytometry (an ELISA-based quantitative assay that allows determination of molar transport rates is described in ref.5).